Cyclophosphamide induced anemia in Wistar rats: can it be prevented by Sajna (Moringaoleifera)? - Fatema, Farhana; Nahar, Sharmin; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2020)
Background: Chemotherapy-induced anemia is a multifactorial challenge to the treatment of malignancy. Herbal medicine may help totreat such anemia due to its natural compatibility. Moringaoleifera (Sajna), is well known for preventing and curing anemia. Objective: To evaluate the preventive effect of aqueous extract of Moringaoleiferaleaf (AEMOL) on cyclophosphamide (CP) induced anemia in Wistar rats. Method: The experimental study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka from July 2015 to June 2016. Thirty Wistar ratsof both sexes weighing 175±25 gm were grouped as A[normal saline (1ml/kg); oral],and B [CP (3mg/kg);i. p.], C[AEMOL (300mg/kg);oral], D [AEMOL(300mg/kg); oral and CP(3 mg / kg) i. p. simultaneously for 14 consecutive days] and E [AEMOL(300mg/kg); oralfor 14 consecutive days and CP(30mg/ kg); i. p. on 12th, 13th,14th day] with 6 rats in each group.All the rats had free access to food and distilled water during the period of acclimatization (seven days) and experiment(fourteen days).Total count(TC)) of RBC, hemoglobin (Hb) level and packed cell volume (PCV)were estimated to assess anemia in all rats before and after experiment. The statistical analyses were done by one way ANOVA followed by Bonferroni post hoc test where p<0.05 was accepted as level of significance. Result: The mean TCof RBC, Hb% and PCV were significantly (p<0.001) lower in CP treated rats (group B), in comparison to all other rats of different groups (A, C, D and E). In addition, all these three variables were significantly higher in AEMOLtreated group(C) compared to saline treated rats (A)but almost similar in rats with two groups of different dose schedule of AEMOL and CP (D, E). Conclusion:From the study, it can be concluded that CP induced anemia can be prevented by AEMOL used either simultaneously or in an anticipating manner. J Bangladesh Soc Physiol. 2020, June; 15(1): 11-16